Literary theories : a reader and guide - Wolfreys, Julian, 1958- (Edinburgh University Press, 1999)
An introductory text covering structuralism, reader-response theory, post-structuralism, new historicism, postcolonialism and gay studies and queer theory. -- Provided by publisher.